Estimating product efficiency through a hedonic pricing best practice frontier - Ruben Arrondo; Nuria Garcia; Eduardo González Fidalgo (BRQ Business Research Quarterly, 2018)
A complex critical decision in marketing and economics is pricing. Finding the right price for a product requires careful assessment of the product attributes. Product efficiency evaluation establishes the relative appeal of a product, when compared with the observable attributes and prices of competing products. The main contribution of this paper is combining hedonic pricing with frontier analysis to estimate product efficiency, which is a novel approach. We apply this method to the running shoes market. We find four attributes as main drivers of price: Stability, Cushioning, Flexibility and Response. The model also identifies overpriced products and predicts the price reductions needed in order to be comparatively competitive, a prerequisite for overall business performance. Our results show the dynamics of price adjustments in the market. Overpriced products adjust prices down quickly gaining comparative appeal. Another interesting finding is that product efficiency strongly correlates with the evaluations made by independent experts."
Keywords: 650; Hedonic pricing; Stochastic frontier analysis; Product efficiency; Running shoes